Gubernaculum tract: A guide for determining odontogenic lesions - Dhruvesh Gupta; Nagaraju Kamarthi; Suhasini P Gotur; Khushboo Bhalla (Wolters Kluwer Medknow Publications, 2020)
Determining the etiology of the lesions either be in the bone or soft tissues becomes an imperative factor for treating the lesions. Maxillo-mandibular jaw lesions are also affected by many lesions be it odontogenic or nonodontogenic. The appearance of both these lesions can have a varied clinical and radiographic presentation. Therefore, determining the pathogenesis becomes the most imperative criteria for determining the additional investigations and treatment protocol. We hereby are presenting a radiographic finding of association of gubernaculum tract in determining the odontogenic origin lesions.